Gimmicks and Habitus: An Analysis of Socio-Cultural Reproduction in the 2024 Indonesian Vice-Presidential Debate - Ririt Yuniar; Suluh Gembyeng Ciptadi; Nathalia Perdhani Soemantri (CV. Media Digital Publikasi Indonesia, 2026)
The 2024 Indonesian vice-presidential debate appears to feature more gimmicks than substantive discussions of the candidates’ visions and missions. This study aims to examine how the vice-presidential candidates reproduce socio-cultural values through their performances during the debate. Using Bourdieu’s theoretical framework of habitus (field, arena, and strategy), this research seeks to explore how the candidates construct the reproduction of socio-cultural values through their habitual practices. The study employs a qualitative method with text analysis as the primary data collection technique. The data analyzed consists of textual transcriptions from the fourth vice-presidential debate, broadcast on the official YouTube channel of the General Elections Commission (KPU) of the Republic of Indonesia, and used voyant.tools to determine dominant words from the comments. The findings indicate that the candidates’ habitus determines the type of socio-cultural reproduction displayed during the debate. The result of this research identified three key patterns: First, Attacking-question gimmicks reinforced dominance and control over debate narratives. Second, Emotional and satirical gimmicks provoked opponents and audiences while diverting attention from substantive content. Third, Youth-oriented gimmicks leveraged humor and relatability to attract younger voters. These performances reproduced a political reality that emphasized style over substance, signaling a shift toward performative politics in which image and symbolism dominate over ideas (knowledge), ethics, wisdom, and maturity in public speaking. This research is also relevant for researchers, political strategists, and media analysts.